2010
DOI: 10.1016/j.pain.2010.08.015
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of demographic and psychosocial variables to pain-related outcomes in a rural chronic pain population

Abstract: Rural residency and low socioeconomic status (SES) are associated with increased likelihood of chronic pain. Other demographics are also differentially associated with the experience of pain. This study examines the relations between demographic and pain-related variables in a virtually unstudied population of rural Alabama chronic pain patients. One-hundred-and-fifteen patients completed validated measures of pain catastrophizing, depression, pain intensity, pain interference, perceived disability, and life s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
70
3
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 101 publications
9
70
3
2
Order By: Relevance
“…Differences in physician prescribing practices and use of prescription monitoring programs between geographic areas may contribute to the community supply of certain drugs (30,48,49). One study suggested that methadone is more commonly prescribed in rural areas for chronic pain than in urban areas (50).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in physician prescribing practices and use of prescription monitoring programs between geographic areas may contribute to the community supply of certain drugs (30,48,49). One study suggested that methadone is more commonly prescribed in rural areas for chronic pain than in urban areas (50).…”
Section: Discussionmentioning
confidence: 99%
“…The recently reported RCT examined the feasibility and efficacy of a literacyadapted, culturally sensitive group CBT program in comparison to a similarly adapted Pain Education intervention [35]. Participants were rural, predominantly African-American people with chronic pain, and characterized by low socioeconomic status (SES) and low literacy [36]. Typically found to be largely inert, systematic reviews have reported no clinically significant effect of group education-based programs, such as "back schools [37][38][39]."…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence increases with age. It affects physical and psychological health, is associated with increased social isolation (Clarke & Iphofen 2008) and the incidence is reportedly higher in rural than urban areas (Hoffman et al 2002;Day & Thorn 2010;Reitsma et al 2012). Specialist pain services and patient self-help group meetings tend to be physically located in urban centres, presenting access challenges to rural patients.…”
Section: Research Contextmentioning
confidence: 99%